2013
DOI: 10.1016/j.stem.2013.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Opposing Regulation of Sox2 by Cell-Cycle Effectors E2f3a and E2f3b in Neural Stem Cells

Abstract: The mechanisms through which cell-cycle control and cell-fate decisions are coordinated in proliferating stem cell populations are largely unknown. Here, we show that E2f3 isoforms, which control cell-cycle progression in cooperation with the retinoblastoma protein (pRb), have critical effects during developmental and adult neurogenesis. Loss of either E2f3 isoform disrupts Sox2 gene regulation and the balance between precursor maintenance and differentiation in the developing cortex. Both isoforms target the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
79
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 42 publications
1
79
0
1
Order By: Relevance
“…We determined the genomic binding sites of E2f3 and E2f4 in NPCs derived from telencephalic tissue at embryonic day 14.5 (E14.5), a peak stage of cortical neurogenesis. As E2f binding sites are typically found within close proximity of a transcriptional start site (TSS) 8,17,20,24,26 we focused our analysis on promoter regions by coupling chromatin immunoprecipitation (ChIP) using antibodies towards E2f3 and E2f4 (Figure 1a and b) with proximal promoter DNA microarrays (details in Supplementary Text S1). We have validated the specificity of these antibodies previously 8 and here (Supplementary Figure S1 and S2).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We determined the genomic binding sites of E2f3 and E2f4 in NPCs derived from telencephalic tissue at embryonic day 14.5 (E14.5), a peak stage of cortical neurogenesis. As E2f binding sites are typically found within close proximity of a transcriptional start site (TSS) 8,17,20,24,26 we focused our analysis on promoter regions by coupling chromatin immunoprecipitation (ChIP) using antibodies towards E2f3 and E2f4 (Figure 1a and b) with proximal promoter DNA microarrays (details in Supplementary Text S1). We have validated the specificity of these antibodies previously 8 and here (Supplementary Figure S1 and S2).…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, we have previously demonstrated that loss of either E2f3 isoform in NPCs does not result in altered expression or a perceivable change in DNA-binding capacity of the other isoform, nor of other E2f factors. 8 Figure 2 E2f3 and E2f4 bind an overlapping set of gene promoters associated with fundamental NPC fate decisions. (a) Gene Ontology (GO) analysis of E2f3 and E2f4 target genes, expressed as the percentage of all target genes in each group (groups indicated to the right of the graph) with a particular GO annotation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations